Cybersecurity Education Strategies Based on Open-Source Intelligence (OSINT) to Enhance Public Awareness - Taufik Hidayat; Budi Wibowo; Andrie Yuswanto; Annisa Fathul Jannah (International Journal of Science Education and Cultural Studies, 2025)
In today’s rapidly evolving digital landscape, cybersecurity threats are escalating in both frequency and complexity, which points to the urgent need for effective educational approaches to enhance public awareness. Open-Source Intelligence (OSINT), which leverages publicly available information, offers a practical framework for identifying and understanding cyber risks. This study proposes the design, implementation, and evaluation of an OSINT-based cybersecurity education strategy aimed at non-technical audiences. Employing a mixed-methods approach including literature review, module development, and surveys, this research measures the strategy’s effectiveness in improving cybersecurity comprehension. The results indicate that the OSINT-based educational approach significantly enhances participants’ understanding of cyber risks, yielding an average increase of 35% in comprehension scores. Furthermore, the integration of real-world OSINT demonstrations makes cybersecurity threats more tangible and personally relevant, thereby motivating proactive preventive behavior. In conclusion, incorporating OSINT into cybersecurity education provides an effective and scalable strategy for improving public awareness and resilience against modern digital threats.